Fabrication and characterization of modified ZnO-kapok fiber for separating surfactant-free oil-in-water emulsions - Hamidon, M. Adam Bukhori; Hussin, R.; Yunos, M. Z.; Ainuddin, A.R. (2024)
. Natural sorbents have several benefits, including high sorption capacity, superior biodegradability, and low cost. Kapok is one of the natural fibers that can be used as absorbent material. These distinctive qualities give kapok fibers greater oil sorption capacity than other oil sorbents currently on the market. However, it is difficult to hold oil properly due to its waxy coating and smooth fiber surface. Thus, in this study, the rough surface fiber has been coated using ZnO via the hydrothermal method. Considering that ZnO is instinctually hydrophilic, this modification of the fiber compounds increases the adsorption of oil in fiber. The surface morphology interaction has been proven with an experiment using a scanning electron microscope (SEM) for morphology investigation, Fourier-transform infrared spectroscopy (FTIR) for identifying organic or inorganic materials, and physical interaction (contact angle analysis). The results obtained display a significant difference between modified kapok fiber with ZnO and raw kapok fiber. The FTIR analysis shows that the modified kapok exhibits the peak's level of intensity at 3268.88 cm-1 (stretching vibration peak of surface –OH decreases obviously as compared with that of raw kapok fiber, an absorption peak (symmetric stretching vibration of Zn–O–Zn) is observed at 652.28 cm-1. These results suggested that the whole sum of –OH was diminished, and hydrophobic ZnO nanoparticles were developed on the kapok fiber's surface. A surface morphology analysis using SEM shows that ZnO particles are present on the kapok fiber surface while comparing it to the raw kapok. Modified kapok shows a higher contact angle (138°) compared to raw kapok (125.5°). This can conclude that the kapok fiber modification was successfully achieved using the hydrothermal method